Peningkatan Kompetensi Profesional Guru PAUD Melalui Penerapan Media Storybook Berbasis Augmented Reality - Dyah Sulistyaningrum Indrawati, Cicilia; Subarno, Anton; Risanti Langgi, Novedi; Berdha Krismona, Elwas; Ridhani, Jovita (Universitas Sahid Surakarta, 2025)
The community service program aims to improve the professional competence of PAUD teachers in providing financial education to early childhood students. The training was conducted in three stages: pre-training, implementation, and evaluation. The training activities were carried out by providing materials related to financial education, learning models and methods, learning media, and practical use of AR-based storybooks for financial education learning at the PAUD level. The three-day training activity impacted the professional competence of PAUD teachers. The asymp evidence this.sig value (2-tailed) in the Wilcoxon test, which had a value of 0.003 (<0.05).